What is the impact of cryptocurrencies on financial markets and global trade? - Felix Roth (University of Hamburg, Department of Economics, Senior Lecturer in International Economics, 2024)
This paper starts with brief introductory remarks, providing the underpinning of the academic argument and a summary statement of its main findings. It then elaborates on the evolution of existing cryptocurrencies' market capitalization from 2009 until 2022. Third, the paper investigates the economic nature of cryptocurrencies and discusses whether they are money. Fourth, it will discuss the direct and indirect impact of cryptocurrencies on financial markets and global trade. Fifth, the paper offers two main conclusions.
Keywords: 330